Brexit and Muslims in Postnormal Times. Issue 5 (2nd November 2018) - Miah, Shamim
Abstract: Papers are full with debates and opinions on Brexit; yet despite this seemingly endless commentary nothing seems to make any sense. The debates associated with Brexit seems to imply that we can 'control' or even 'manage' through this turbulent period with ideas of progress, change and development. Brexit seems to embody and reflect a period which many critical observers have described as the Postnormal Time a period 'where old orthodoxies are dying, new ones have not yet emerged, and nothing really makes sense'. More crucially, it is a period 'when little out there can be trusted or gives us confidence' or more importantly, the spirit of our age, is characterised by uncertainty, rapid change, realignment of power, upheaval and chaotic behaviour.